Une expérimentation de la classe renversée dans l’enseignement de la grammaire du coréen langue étrangère en contexte universitaire français - Kang, Shin-Tae (Neofilolog, 2025)
During a lecture in a lecture hall, it is clear that there is little interaction between the students and the teacher or among the students themselves, as they remain passive consumers and are minimally active. The inverted classroom is an active pedagogy approach that aims to reverse the structure of courses and roles in class (Cailliez, 2019) to enable better acquisition of knowledge. The inverted classroom approach was applied in a group of 62 French students learning Korean as a foreign language in their third year of university to encourage interactions before and during the class and to make them more active. The students, divided into groups, were tasked with conducting a session in which they explained grammar rules to the entire class. Feedback as collected from them with an anonymous questionnaire. This exercise proved to be enriching in many ways: the active search for resources promoted autonomy, group work fostered interactions and developed engagement and individual responsibility, the satisfaction felt after the presentations in the lecture theater boosted self-confidence, and the creativity of the presentations energized the lecture.